An intervention to assist students with writing their dissertations and theses - Singh, S (South African Journal of Higher Education, 2011)
An inadequate number of suitably qualified and experienced supervisors, an increase in the number of students, uncertainty regarding the suitability of supervision and academic rigour in dissertations and theses make it difficult to produce quality graduates within the prescribed time-frame as stipulated by the Department of Education. By implication, a strategy is needed to help both students and supervisors overcome these difficulties and produce quality research within the minimum time-frames. In this article, an intervention to assist students with writing their postgraduate research is presented and the need, planning, validation and implementation thereof are described. Reflection, inductive reasoning and observation initiated the need for this study and formed part of the needs assessment for the intervention. A template was designed as the intervention and was used as a guideline for students to use, presenting the basic format pertinent to writing dissertations heses. To evaluate the intervention, a questionnaire was applied to ascertain students’ opinions about the intervention and was validated using facevalidity. Responses were deemed reliable using the internal consistency for determining reliability. The study concluded that an intervention such as the template is beneficial and is an improvement from the traditional style of supervision and text-book teaching.